Spanish Republican News
001-0032-001 SPANISH REPUBLICAN NEWS STOP PRESS London, September 13, 1945 TWO HEROES OF THE SPANISH REPUBLICAN ARMY CONDEMNED TO DEATH BY FRANCO THEIR LIVES CAN BE SAVED IF BRITISH DEMOCRATIC ORGANISATIONS AND PEOPLE ACT QUICKLY TO PREVENT THIS NEW CRIME OF FASCISM. The help of all British people who are friends of Republican Spain is asked to save the lives of two leading Anti-Fascist Spaniards, Santiago Alvarez, formerly Commissar of the 5th Spanish Republican Army and Sebastian Zapirain, formerly Commissar of the 4th Spanish Republican Army, who have been arrested in Spain and after brutal tortures by the Falangist police have been condemned to death. Santiago Alvarez was a member of the Republican Army since the first day of the war in Spain. His courage, intelligence and self-denial rapidly brought him the confidence and love of the military leaders and soldiers alike. There was not one important battle in Spain which his Unit did not participate. During the Defence of Madrid, his unit was one of the foremost factors in saving the capital of Spain. He took part in the battle of Guadalajara, in which Mussolini's battalions suffered their celebrated defeat. Alvarez was one of the leaders who most distinguished themselves in the battle of the Ebro. His name is bound up with the whole history of the Republican Army. Sebastian Zapirain belongs to one Republican Basque family. Like Alvarez, he was Commissar of an Army Corps in the Battle of Guadalajara. His activities were chiefly confined to the central and southern regions of the fighting. These two Spanish Republicans by their record of struggle against Fascism gained the hatred of the Spanish Hitlerites who now try to revenge themselves against them in accordance with the ever-growing policy of terror against the Spanish people. Alvarez and Zapirain have a magnificent record of struggle against Fascism; the effort to save their lives is an essential act of solidarity on the part of all freedom-loving peoples. 292/946/1/32